2013
DOI: 10.1590/1679-775720130046
|View full text |Cite
|
Sign up to set email alerts
|

Impact of removable partial denture prosthesis on chewing efficiency

Abstract: Removable partial denture prostheses are still being used for anatomic, medical and economic reasons. However, the impact on chewing parameters is poorly described.ObjectivesThe objective of this study was to estimate the impact of removable partial denture prosthesis on masticatory parameters.Material and MethodsNineteen removable partial denture prosthesis (RPDP) wearers participated in the study. Among them, 10 subjects were Kennedy Class III partially edentulous and 9 with posterior edentulism (Class I). A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0
10

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 17 publications
(33 reference statements)
4
36
0
10
Order By: Relevance
“…19 In 4 studies X 50 was determined after a given number of chewing strokes; one study determined D 50 , which is equivalent to X 50 until swallowing. 22 Three studies 22,24,25 also reported on chewing frequency and 2 studies 23,26 on maximum bite force.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…19 In 4 studies X 50 was determined after a given number of chewing strokes; one study determined D 50 , which is equivalent to X 50 until swallowing. 22 Three studies 22,24,25 also reported on chewing frequency and 2 studies 23,26 on maximum bite force.…”
Section: Resultsmentioning
confidence: 99%
“…28 Three papers reported additionally chewing frequency data. Chewing frequencies were expressed as chewing strokes per second, 22 chewing stokes per minute, 25 or time needed for 20 chewing strokes. 24 If applicable the outcomes were converted to chewing strokes per second (Table 4).…”
Section: Comminuting Testsmentioning
confidence: 99%
“…Bessadet et al 14 in which masticatory ability and efficiency showed a significant increase in adapted prostheses after a given time. Retention problems and RPD stability can explain lower MP in the MP1 condition as they directly affect the physiology of mastication.…”
Section: Discussionmentioning
confidence: 97%
“…17 Num outro estudo que avaliou a função mastigatória dos portadores de prótese parcial removível, concluíram que o diâmetro geométrico médio das partículas destes indivíduos permanece acima do indicador normativo mastigatório. 18 O objetivo do presente estudo é realizar uma análise comparativa da performance mastigatória entre os doentes portadores de prótese parcial removível acrílica e esquelé-tica, existindo a hipótese nula de não haver diferença da performance mastigatória entre os utilizadores de PPR acrí-lica e esquelética.…”
Section: Introductionunclassified